العرف بين الوظيفة التشريعية وإشكاليات التحول الاجتماعي - رحماني، إبراهيم (الجامعة الإسلامية العالمية - مجمع البحوث الاسلامية, 2015)
Custom occupies an acknowledged status in Islamic law. This acknowledgement provides due harmony between the function of the law and the social conditions prevailing in the society. This arrangement plays a positive role in guarding the social dynamics against incongruent elements that might hinder healthy direction of social behavior. According to the writer, the due status of custom in the body of the Shar‘ah is traceable to the basic sources of the Qur’n and the Sunnah and is not something alien to their legislative scheme. It is therefore, pertinent that while arriving at a legal view of things under the rules of the Shar‘ah, due regard is given to those healthy customs that are compatible with the moral purposes of the Shar‘ah. At the same time, it is necessary that such social customs as are in concord with the moral vision of the Shar‘ah should continue and those that are in disharmony with it should be discouraged from making inroads in the society
Keywords: العرف -- القوانين والتشريعات -- الشريعة الإسلامية -- التحول الاجتماعي